Early lean mass sparing effect of high-protein diet with excess leucine during long-term bed rest in women - Vinci, Pierandrea; Di Girolamo, Filippo Giorgio; Mangogna, Alessandro; Mearelli, Filippo; Nunnari, Alessio; Fiotti, Nicola; Giordano, Mauro; Bareille, Marie-Pierre; Biolo, Gianni (Frontiers in Nutrition, 2022)
Muscle inactivity leads to muscle atrophy. Leucine is known to inhibit protein degradation and to promote protein synthesis in skeletal muscle. We tested the ability of a high-protein diet enriched with branched-chain amino acids (BCAAs) to prevent muscle atrophy during long-term bed rest (BR). We determined body composition (using dual energy x-ray absorptiometry) at baseline and every 2-weeks during 60 days of BR in 16 healthy young women. Nitrogen (N) balance was assessed daily as the difference between N intake and N urinary excretion. The subjects were randomized into two groups: one received a conventional diet (1.1 ± 0.03 g protein/kg, 4.9 ± 0.3 g leucine per day) and the other a high protein, BCAA-enriched regimen (1.6 ± 0.03 g protein-amino acid/kg, 11.4 ± 0.6 g leucine per day). There were significant BR and BR × diet interaction effects on changes in lean body mass (LBM) and N balance throughout the experimental period (repeated measures ANCOVA). During the first 15 days of BR, lean mass decreased by 4.1 ± 0.9 and 2.4 ± 2.1% (p < 0.05) in the conventional and high protein-BCAA diet groups, respectively, while at the end of the 60-day BR, LBM decreased similarly in the two groups by 7.4 ± 0.7 and 6.8 ± 2.4%. During the first 15 days of BR, mean N balance was 2.5 times greater (p < 0.05) in subjects on the high protein-BCAA diet than in those on the conventional diet, while we did not find significant differences during the following time intervals. In conclusion, during 60 days of BR in females, a high protein-BCAA diet was associated with an early protein-LBM sparing effect, which ceased in the medium and long term.